The investigation of the correlation between diastasis recti and the second stage of labor - Çintesun, Ersin; Aydoğdu, Meltem; Çelik, Çetin (Perinatal Medicine Foundation, 2020)
Objective In our study, we investigated whether the distance between rectus abdominis muscles is correlated with the second stage of labor or not. Methods This is a prospective study conducted on the patients who underwent spontaneous vaginal delivery in our clinic between September 1, 2019 and December 31, 2019. Since these measurements were difficult during pregnancy, they were done after the delivery within postpartum 48 hours. The measurements were done on three anatomic areas, and the distance between rectus abdominis muscles and the thickest rectus muscle were measured by superficial ultrasonography. Xiphoid level, and 2 cm above and below the umbilical area were selected as measurement sites. Afterwards, the partographs in the patient files were checked to calculate the duration of the second stage of labor in minutes, and the correlation between these two values was calculated. The analyses of the patients collected for the study were calculated separately as primiparous and multiparous analyses. Results The data of 57 primigravid patients and 63 multigravid patients were compared. In the primigravid patients, there was a statistically significant weak correlation between the week of gestation, fetal weight and the distance between rectus muscles above xiphoid level and the second stage of labor (p<0.05; r=0.351, 0.369, and 0.336, respectively). No significant correlation was found between other ultrasonographic variables. There was a statistically significant weak correlation between the number of abortion and the second stage of labor in multigravid patients (p=0.002, r=0.390). No significant correlation was found between the rectus muscles and fetal data and the second stage of labor in multigravid patients (p>0.05). Conclusion There was a significant correlation between the second stage of labor and the diastasis recti at the xiphoid level in primiparous patients. Further studies investigating the diastasis recti and intraabdominal pressure would help to determine the impact on the second stage of labor directly.